Physician-patient agreement on physicians’ communication skills and visit satisfaction in dermatology clinics: a one-with-many design - Zuzanna Kwissa-Gajewska; Aleksandra Kroemeke (Health Psychology Report, 2021)
Introduction There is limited research on physician–patient communication skills that covers both sides of the relationship. The aim of this study was to explore two indicators of effective physician-patient communication: the agreement of physicians’ and patients’ perspectives of physicians’ communication skills in outpatient visits to dermatology clinics and the relationship of these perceptions of the consultation with their visit satisfaction.